Nuevo Moda garments education and conservation facility - Pascua, Kolleen R. (College of Architecture, University of the Philippines Diliman, 2019)
Nuevo Moda is a garments education and conservation facility. It has interactive workshop spaces and lecture rooms as well as in-house garments recycling and processing rooms for Taytay's aspiring dressmakers and fashion designers. It will utilize the municipality's garment resources not only for production but also for fashion design and education. Moreover, the project also aims to establish Taytay as the pioneer in garments conservation by using recycling and upcycling methods, which can hopefully promote sustainability in the fashion and garments industry in the country. This will further solidify Taytay's image as the leading garments center in the Philippines. The project has three major parts which address a particular issue when it comes to garments, namely: Garments Recycling Facility (Environment); Dressmaking Training Center (Education); Sustainable Garments Center (Empowerment).